Territorial planning and adaptation to global changes. A critical analysis of the French State doctrine on the coast of the Gulf of Lion - Brun, Alexandre; Maléfant, Llewella (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2023)
The Mediterranean coast condition is worrying. The Gulf of Lion coast lower and sandy areas, densely urbanized, are particularly exposed to erosion. In addition, this coastline will experience by 2100 an increase in salt water intrusions, floods by marine submersion and damage to infrastructure due to sea level rise. The State first “left it to the developers” at the end of the 19th century, then decided to build new seaside resorts within the ‘Mission Racine’ the framework in the second half of the 20th century. The State now defends a “retreat doctrine” by relocating activities and people further away from the sea. However, this doctrine is opposed by economic actors and especially by local elected representatives, who have become the real architects of planning policies as a result of the 80’ decentralisation. The adaptation of this very touristy coast, which was an international laboratory of architectural and urban innovation during the 1960s, therefore seems compromised. Neither the local planning tools nor even the regional coastal management strategy can reconcile economic development and resilient urban planning in the absence of coastal governance.